Archéologie de la Grande Guerre : les recherches archéologiques sur les gares régulatrices françaises et américaines de Marcilly-sur-Tille, 1914/1919 (Côte-d’Or) - Frédéric Devevey (In Situ, 2014)
Situated at the frontier between the departments of the Côte d’Or and the Haute-Marne, the Marcilly-sur-Tille railway station owes its existence to the East railway company and to the late nineteenth-century development of railway traffic on the line between Dijon and Neufchateau. The outbreak of war in 1914 was to give this station a new and vital role. From 2 August 1914, the station was comprised in the general plans for mobilisation and became a ‘gare régulatrice de communication’, a regulatory communications station, according to the military designation of the time. Following heritage regulations, an operation of archaeological diagnosis was carried out on the site in April 2011. This article presents the first findings of this archaeological operation, the first of its kind in the Burgundy region.